Biases in the production of knowledge on ecosystem services and poverty alleviation. Issue 6 (17th November 2021) - Corbera, Esteve; Maestre-Andrés, Sara; Calvet-Mir, Laura; Brockington, Dan; Howe, Caroline; Adams, William M.
Abstract: Research into the relationship between ecosystem services and human well-being, including poverty alleviation, has blossomed. However, little is known about who has produced this knowledge, what collaborative patterns and institutional and funding conditions have underpinned it, or what implications these matters may have. To investigate the potential implications of such production for conservation science and practice, we address this by developing a social network analysis of the most prolific writers in the production of knowledge about ecosystem services and poverty alleviation. We show that 70% of these authors are men, most are trained in either the biological sciences or economics and almost none in the humanities. Eighty per cent of authors obtained their PhD from universities in the EU or the USA, and they are currently employed in these regions. The co-authorship network is strongly collaborative, without dominant authors, and with the top 30 most cited scholars being based in the USA and co-authoring frequently. These findings suggest, firstly, that the production of knowledge on ecosystem services and poverty alleviation research has the same geographical and gender biases that characterize knowledge production in other scientific areas and, secondly, that there is an expertise bias that also characterizes other environmental matters. This is despite the fact that the research field of ecosystem services and poverty alleviation, by its nature, requires a multidisciplinary lens. This could be overcome through promoting more extensive collaboration and knowledge co-production.